Hydrochemical properties of springs Slatinski Izvor and Solenica (Republic of Macedonia) - Biljana Gichevski; Slavčo Hristovski; Vojo Mirčovski; Blažo Boev (Acta Carsologica, 2015)
Hydrochemical properties of water samples from the Slatinski Izvor spring and Solenica spring were analyzed during the period between December 2011 – November 2013. The wider area around the springs belongs to two tectonic units. The first is the Pelagonian horst-anticlinorium and is composed of carbonate rocks. The second is the Western Macedonian zone, and it is composed of non-carbonate rocks. The Slatinski Izvor spring is located on the Pelagonian horst anticlinorium, and the Solenica spring is situated on a fault which separates the two tectonic units. The measurements of the temperature, conductivity and the hydrochemical analysis indicate that both springs have different hydrochemical properties. The major cations in the Slatinski Izvor spring were Ca2+ and Mg2+, and anions were HCO3- and SO42-, the water had temporary hardness and it belongs to calcium hydrogencarbonate water type. The Slatinski Izvor spring had typical shallow and fresh water. The major cations in the Solenica spring were Na+ and Ca2+, and anions were Cl- and HCO3-. The water belongs to NaCl water type which is typical of deep ancient ground water.